AB0277 Trace – Therapy Adherence in Patients with Rheumatoid Arthritis – Influence Factors and Correlates: A Consensus-Based Study Protocol and Study Performance. (9th June 2015) - Kuipers, J.G.; Rüffer, J.U.; Zeman, F.; Müller, K.; Koller, M.
Abstract : Background: Adherence to the treatment of rheumatoid arthritis (RA) is an essential component for therapeutic success. The factors contributing to high or low adherence are still under debate. Objectives: Investigation of the influence of socio-demographic variables, therapy protocol, fatigue, and various psychosocial variables on adherence to RA-therapy. Methods: Development of the study protocol was based on a consensus process that included rheumatologists, trial methodologists, data managers and representatives of a contract research organization (CRO). The decision was to use a survey methodology. A survey was undertaken that included a representative, nationwide German sample of physicians treating rheumatological patients. Physicians received an invitation letter and in case of a positive response they received a package of questionnaires. There were two types of questionnaires: the physician questionnaire asked for some basic patient demographic information (age, gender), physician-assessed Disease Activity Score (DAS 28) and a detailed account of the current medication. The patient questionnaire tapped into additional demographic information (level of education, profession, family status) as well as compliance (CQR5) and satisfaction with treatment, quality of life (SF-12), health-related competence (HELP) and activities of daily living (MDHAQ). The survey was anonymous, but each physician questionnaire and its corresponding patient questionnaire contained the same identification number so that they could be linked in the database. Results: This preliminary data analysis is based on 615 physician questionnaires and 580 patient questionnaires. There was a good and representative spread across geographic regions in Germany. An initial inspection of the questionnaires indicated that the number of missing items was low (<1%). Preliminary results suggest that mean age of all patients (n=580) was 60 (SD 12) years and 423 of 580 patients were women (72%). The majority of patients was insured at a statutory health insurance (n=532, 92%). Physicians (n=615) classified disease activity as low active (DAS28≤3.2) in 67%, as moderate active (3.25.1) in 4% of the patients. Patients' self-reported adherence was high on the CQR5 (possible range 5 to 20) with a mean of 17.5 (SD 3.3), but did not match physicians' rating of patient-adherence (r=0.1, p=0.035). Conclusions: This study promises to gain insights into the adherence to medical therapy in a large sample of patients affected with rheumatoid arthritis (RA). These findings may help to detect patients who are at risk to comply with treatment and thus to optimize patient education and counseling. References: Rauscher V, Englbrecht M, van der Heijde D, Schett G, Hueber AJ. J Rheumatol. 2015 Jan 15. pii: jrheum.140982. [Epub ahead of print] Zwikker HE, van Dulmen S, den Broeder AA, van den Bemt BJ, van den Ende CH. Patient Prefer Adherence. 2014 Nov 25;8:1635-45. doi: 10.2147/PPA.S66849. eCollection 2014. Gadallah MA, Boulos DN, Gebrel A, Dewedar S, Morisky DE. Am J Med Sci. 2014 Dec 3. [Epub ahead of print] Acknowledgements: This study is supported by a grant of CHUGAI Pharma Disclosure of Interest: J. Kuipers Grant/research support from: Research grant by Chugai Pharma, J. Rüffer Grant/research support from: Research grant by Chugai Pharma, F. Zeman Grant/research support from: Research grant by Chugai Pharma, K. Müller Grant/research support from: Research grant by Chugai Pharma, M. Koller Grant/research support from: Research grant by Chugai Pharma